A Flavonoid Glycoside Compound Isolated from Macaranga gigantifolia Merr Leaves - Gian Primahana; Akhmad Darmawan (The Journal of Pure and Applied Chemistry Research, 2017)
Apigenin-8-C-glycoside (1), a flavonoid glycoside compound has been isolated from the leaves of Macaranga gigantifolia Merr. Isolation and purification conducted by chromatography methods and chemical structure characterization carried out by spectroscopic methods. Cytotoxicity of Apigenin-8-C-glycoside has been tested against Murine leukemia P-388 cell lines and has moderate activity with IC50 values 55.4 μg/mL.